Assessing Patients with Asymptomatic Retinal Emboli Detected at Retinal Screening. Issue 2 (December 2016) - Ahmmed, Afsara; Carey, Peter; Steel, David; Sandinha, Teresa
Abstract Introduction Asymptomatic retinal emboli have been associated with diabetes, the presence of significant carotid artery stenosis (≥70%) and an increased risk of stroke. However, there is no clear guidance on how best to investigate and manage patients found to have asymptomatic retinal emboli. Therefore, this study aimed to assess the incidence of significant carotid artery stenosis in patients found to have asymptomatic retinal emboli at diabetic retinopathy screening, and to examine disease management approaches among these patients. Methods Patients with new retinal emboli visible at diabetic retinopathy screening were referred to a medical retinopathy clinic and underwent examinations according to a standardized protocol, including carotid Doppler ultrasound and echocardiography. Case notes of patients referred between January 2013 and April 2014 were reviewed. Results of investigations, medication changes and the number of patients who underwent relevant surgical interventions were noted. Results Retinal emboli were present in 44 of 13, 643 people screened (0.32%). Full data were available for 39 patients. Twenty-two patients (56%) had relevant medication changes. Nine (23%) patients had significant carotid artery stenosis. One underwent carotid endarterectomy, and eight received maximal medical therapy. Conclusion Significant carotid artery stenosis was not uncommon in patients with incident retinal emboli at retinal screening. The referral and investigation protocols identified individuals at risk of cerebrovascular events and led to optimized management. Pathways utilizing Doppler ultrasound and physician referral should be more widely implemented.